Microorganisms in the Treatment of Cancer: Advantages and Limitations - Klaudia Łukasiewicz; Marek Fol (Journal of Immunology Research)
Cancer remains one of the major challenges of the 21st century. The increasing numbers of cases are not accompanied by adequate progress in therapy. The standard methods of treatment often do not lead to the expected effects. Therefore, it is extremely important to find new, more effective treatments. One of the most promising research directions is immunotherapy, including the use of specific types of microorganisms. This type of treatment is expected to stimulate the immune system for the selective elimination of cancer cells. The research results seem to be promising and show the intensive activation of the immune response as a result of bacterial stimulation. In addition, it is possible to use microorganisms in many different ways, based on their specific properties, that is, toxin production, anaerobic lifestyle, or binding substances that can be delivered to a specific location (vectors). This paper provides an overview of selected microorganisms which are already in use or that are in the experimental phase. Just like any other therapy, the use of microbes for cancer treatment also has some disadvantages. Nevertheless, this kind of treatment can supplement conventional anticancer therapy, giving cancer patients a chance and hope of recovery.